2016
DOI: 10.1185/03007995.2016.1157462
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of delaying treatment intensification in type 2 diabetes: evidence from a UK database

Abstract: Patients who were rapidly intensified achieved a maintained reduction in HbA1c faster than those with delayed intensification or no second-line therapy, despite a higher baseline HbA1c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Articles mainly reported data from cohort studies, using data from medical records or chart reviews, or from claims, clinical research or administrative databases. Four articles reported results from cross‐sectional studies, and the data were collected using provider questionnaires or surveys . A single publication reported results from a randomized clinical trial that evaluated the impact of physician education on the management of individuals with type 2 diabetes, and another provided results from a post hoc analysis of a randomized controlled trial …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in previous studies in populations initiating BI, these patients were characterized by elevated HbA1c levels at baseline; a high proportion of patients initiated BI with HbA1c > 9.0%, highlighting a disconnect between real‐world clinical practice and recommendations in clinical guidelines, and indicating a delay in initiating insulin far beyond the point of need. This is of critical concern given the need for tight glycaemic control and/or appropriate treatment intensification to reduce the risk of diabetes‐related complications, to help preserve β‐cell function and to achieve long‐term glycaemic goals . As such, the success of BI‐supported oral therapy is dependent on timely initiation during the natural history of T2DM in the individual patient.…”
Section: Discussionmentioning
confidence: 99%